The skill-biased effects of exchange rate fluctuations - Boris Kaiser; Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2015)
This paper examines the linkages between real exchange rate movements and firms' skill demand. Real exchange rate movements may affect unskilled workers differently than skilled workers because of skill-specific adjustment costs, or because exchange rates lead to changes in relative factor prices and firms' competition intensity. Using panel data on Swiss manufacturers, we find that an appreciation increases high-skilled and reduces low-skilled employment in most firms, while total employment remains roughly unchanged. We find evidence that exchange rates influence firms' skill intensity because they affect outsourcing activities, innovation efforts, and firms' compensation schemes.
Keywords: E24; F16; F31; 330; Labor Demand; Skill Intensity; Employment; Real Exchange Rates; Firms' Foreign Exposure